TEKANAN PNEUMATIK PEMBUKA DAN PENUTUP PINTU PENCURAH ADONAN MESIN PENCETAK KERIPIK TEMPE - Bambang Sugiyanto; Abd Rahman; Nisfan Bahri; Supriyanto; Nursuar (JURNAL TEKNOLOGI PERTANIAN, 2022)
Tempe is a typical Indonesian food which is widely consumed by the public as a side dish to increase appetite, as well as as a snack that has its own flavor for its fans. Tempe artisans in Karanganyar Village, Secanggang District, Langkat Regency, North Sumatra Province still maintain the method of making tempe chips manually by printing tempe chips one by one while they are still dough. will have a distinctive taste. This research examines the prototype of a tempe chip printing machine using a pneumatic system in the process of pouring dough onto molds in bulk which can replace manual work. The results of the study obtained the pressure value to open and close the dough pouring door ranging from 1.2 bar to 1,6 bar which resulted in the best batter pouring over the mold patron, this is expected to be a reference in developing/designing tempe chip printing machines, especially printing machines semi-automatic tempe chips which are controlled using pneumatic media.